AN OPEN LABEL, RANDOMIZED, COMPARATIVE, PARALLEL GROUP, SINGLE CENTER STUDY TO EVALUATE SAFETY AND EFFICACY OF ANO SPRAY IN A COMPARISON WITH BETADINE SOLUTION APPLICATION IN ACUTE PERINEUM WOUNDS (AYUSHDHARA, 2018)
Perianal wound are common post-surgical treatment of perianal diseases and in disease near perianal region. In current existing treatment modalities there is no significant number of patients who get relief from perianal wound. We have conducted an open label, randomized, parallel group and single center study to observe safety and efficacy of Ano Spray. Total 30 patients were randomized on Ano spray group and betadine solution group (1:1 ratio). All the patients were advised to apply Ano spray and betadine solution twice daily for 4 weeks. All patients visited center on Day 0, Week 1, 2, 3 and 4. Patient’s quality of life on PAC-QOL & pain was assessed on VAS score on each visit. Local examination was done at each visit for discharge, itching and healing progress. In Ano spray patient’s group wound is significantly healed in lesser time in comparison with Betadine solution group. In both group VAS score for pain was significantly (p< 0.05) improved from baseline Day 0 to Week 4 and significantly improvement observed in Ano spray group. At the end of the study (Week 4), significant (P < 0.05) results were observed in Ano Spray group than Betadine solution group in itching and discharge associated with wound. Excellent overall efficacy and tolerability was observed in patients of both the groups. No adverse event or adverse drug reaction was noted in any patient of both the groups. Study result shows Ano Spray is safe and superior to Betadine Solution in perineum wound healing.